Antimicrobial Activity of Amino Acid-Capped Zinc and Copper Sulphide Nanoparticles. (1st August 2018) - Mofokeng, Thapelo P.; Moloto, Makwena J.; Shumbula, Poslet M.; Nyamukamba, Pardon; Mubiayi, Pierre K.; Takaidza, Samkeliso; Marais, Laurette
Abstract : The synthesis of polydispersed zinc sulphide and copper sulphide nanocrystals capped with polar l -alanine (Aln) and l -aspartic acid (Asp) molecules is reported. The resulting nanocrystals were characterized by UV-visible spectroscopy (UV-Vis), photoluminescence (PL), X-ray diffraction (XRD), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FT-IR). UV-Vis absorption spectra of all samples were blue-shifted from the bulk band edges due to quantum confinement effects. PL emission spectrum of the nanoparticles showed peaks at 453 and 433 nm for Aln-capped ZnS and CuS nanoparticles, respectively, while peaks for Asp-capped ZnS and CuS nanoparticles were observed at 455 and 367 nm, respectively. The average particle sizes for Aln-capped ZnS and Asp-capped ZnS nanoparticles synthesized at 35°C were measured to be 2.88 nm and 1.23 nm, respectively. The antibacterial properties were tested using different strains of both positive and negative bacteria and fungi. It was found that capped-copper sulphide nanoparticles were more effective against the bacteria than capped-zinc sulphide nanoparticles. Staphylococcus aureus (ATCC 25923) was the most susceptible one with an MIC of 0.05 mg/mL for uncapped-CuS nanoparticles while Pseudomonas aeruginosa (ATCC 15442) and Cryptococcus neoformans (ATCC 14116) were the least ones with the MIC of 3.125 mg/mL for both uncapped-CuS and Aln-capped CuS.